The legal convergence of prenuptial agreements: An analysis of the marriage law, Islamic law compilation, and constitutional jurisprudence - Mubarak, Ahmad; Listiana, Novy; Azkia, Nurul; Abduh, Muhamad Rahmani; Ashidiqi, Iqnaul Umam (Priviet Social Sciences Journal, 2026)
A prenuptial agreement is an important instrument in marriage law that regulates agreements between prospective spouses to arrange their rights, obligations, and property prior to marriage. The study of prenuptial agreements is particularly urgent in the modern context, where social and economic dynamics continue to evolve and influence family life. This study aims to examine, from a legal perspective, how prenuptial agreements are regulated in Indonesian civil law, their implementation in society, and their legal implications for the division of property and safeguarding each party's rights following marriage. The research method used is a normative method, using the analysis of legal documents and related literature, as well as case studies to demonstrate how prenuptial agreements are used in practice. The study’s results found that prenuptial agreements possess enforceable legal authority as long as they meet the requirements of a valid agreement according to the Civil Code and applicable laws and regulations, including the Marriage Law. These agreements serve to avoid property disputes at the end of a marriage through divorce or death. However, it is of paramount importance that legal convergence regarding prenuptial agreements is achieved. Similarly, the role of the notary as an authorized official is crucial in providing optimal legal protection. The legal implications of prenuptial agreements are vital for ensuring legal certainty for couples, particularly concerning the division of joint property, which can be adjusted to the parties' wishes in accordance with the initial agreement